A homogeneous database of sunspot areas covering more than 130 years - Balmaceda, Laura Antonia (2009)
The historical record of sunspot areas is a valuable and widely used proxy of solar activity and variability. The Royal Greenwich Observatory regularly measured this and other parameters between 1874 and 1976. After that time records from a number of different observatories are available. These, however, show systematic differences and often have significant gaps. Our goal is to obtain a uniform and complete sunspot area time series by combining different data sets. A homogeneous composite of sunspot areas is essential for different applications in solar physics, among others for irradiance reconstructions. Data recorded simultaneously at different observatories are statistically compared in order to determine the intercalibration factors. Using these data we compile a complete and cross-calibrated time series. The Greenwich data set is used as a basis until 1976, the Russian data (a compilation of observations made at stations in the former USSR) are used between 1977 and 1985, and data compiled by the USAF network are used since 1986. Other data sets (Rome, Yunnan, and Catania) are used to fill up the remaining gaps. Using the final sunspot areas record the Photometric Sunspot Index is calculated. We also show that the use of uncalibrated sunspot areas data sets can seriously affect the estimate of irradiance variations. Our analysis implies that there is no basis for the claim that UV irradiance variations have a much smaller influence on climate than total solar irradiance variations.